Bankıng Funds and the Industrıal Sector in Indonesıa - Medyawati, Henny; Yunanto, Muhamad (Department of Management, Faculty of Economics and Business, Brawijaya University, 2016)
Banking, the blood of any economy, recorded strong growth over the last 5 years in Indonesia, particularly in terms of the volumes of funds collected. The purpose of this research is to examine the indicators of banking, banking technology indicators namely Bank Indonesia-Real Time Gross Settlement (BI-RTGS), industrial sector and services in the Indonesian economy as measured by the nation’s Gross Domestic Product (GDP). This study uses time series data covering 2000 (fourth quarter) to 2014. Testing of time series data using the unit root test and co-integration test, indicated that variables were not stationary at the current level and that the Vector Error Correction Model (VECM) can be applied provided that there is co-integration. The results showed that the GDP responded positivelyto shocksarising from third party funds, assets and BI-RTGS. Negative response was indicated by the loan variables, industry and services. An analysis of variance decomposition indicated that the third party fundshad the largest percentage contribution compared with those attributable to five other variables.